Numerical analysis of wide-field optical imaging with a sub-20 nm resolution based on a meta-sandwich structure - Shun Cao (Nature Portfolio, 2017)
Abstract Biological research requires wide-field optical imaging techniques with resolution down to the nanometer scale to study the biological process in a sub-cell or single molecular level. To meet this requirement, wide-field structured illumination method (WFSIM) has been extensively studied. The resolution of WFSIM is determined by the period of the optical interference pattern. However, in traditional WFSIM this period is diffraction limited so that pattern having periodicity smaller than 100 nm cannot be generated and as a result achieving an imaging resolution better than 50 nm is a great challenge. Here, we demonstrate a wide-field optical nanoimaging method based on a meta-sandwich structure (MSS) model. It is found that this structure can support standing wave surface plasmons interference pattern with a period of only 31 nm for 532 nm wavelength incident light. Furthermore, the potential application of the MSS for wide-field super-resolution imaging is discussed and the simulation results show an imaging resolution of sub-20 nm can be achieved. The demonstrated method paves a new route for the improvement of the wide field optical nanoimaging, which can be applied by biological researchers to study biological process conducted in cell membrane, such as mass transportation and others.